Low Expression Levels of SLC22A12 Indicates a Poor Prognosis and Progresses Clear Cell Renal Cell Carcinoma - Xu, Jiaju; Liu, Yuenan; Liu, Jingchong; Shou, Yi; Xiong, Zhiyong; Xiong, Hairong; Xu, Tianbo; Wang, Qi; Liu, Di; Liang, Huageng; Yang, Hongmei; Yang, Xiong; et al. (Frontiers in Oncology, 2021)
Clear cell renal cell carcinoma (ccRCC) accounts for approximately 4/5 of kidney cancers, and its metastasis in the late stage threatens the life of the patients. The accumulation of minor changes in cellular homeostasis may be one cause of ccRCC, which in turn, results to cellular homeostasis. To this end we downloaded the RNA sequencing and survival data of the kidney renal cell carcinoma (KIRC) cohort from the Cancer Genome Atlas (TCGA) database, finding out 19 kidney-specific differentially expressed genes (DEGs) involved in cellular homeostasis and analyzing them by univariate and multivariate Cox regression analyses. Eventually, Solute Carrier Family 22 Member 12 (SLC22A12) stood out as an independent prognostic predictor in both overall survival (OS) and disease-free survival (DFS). SLC22A12 is low expressed in tumorous tissue compared to normal tissue and patients in low-SLC22A12 group harbor higher pathological stage and worse survival than that of high-SLC22A12 group. In addition, qRT-PCR assay, immunoblotting test (IBT) and immunohistochemical (IHC) analyses of cancer tissues/cells and corresponding normal controls validated the low expression of SLC22A12 in ccRCC. Receiver operator characteristic (ROC) curves showed that the low expression level of SLC22A12 may be a diagnostic indicator of ccRCC (AUC=0.7258; p <0.0001). Gene set enrichment analysis (GSEA) showed that it related the expression level of SLC22A12 to multiple metabolic pathways, cell cycle and tumor-related signaling pathways. GO and KEGG analyses uncovered its influence on transport of multiple organics, ions and hormones, as well as extracellular structure organization. Furthermore, over-expression of SLC22A12 in vitro inhibited the proliferation, migration and invasion of renal cancer cells by regulating PI3K/Akt pathways while knocking out SLC22A12 would reverse it. SLC22A12, as a transporter of many key metabolites, may affect tumor cell survival via its impacts on related metabolites. In conclusion, this study uncovered that SLC22A12 was a promising prognostic and diagnostic biomarker for ccRCC.